Anatomy of web data scraping: ethics, standards, and the troubles of the law - Ugo Pagallo (European Journal of Privacy Law & Technologies, 2023)
The paper examines the ethical and legal issues raised by web scraping technology. Attention is drawn to some landmark rulings to emphasize that jurisdictions such as the US and the EU Member States tackle issues of scraping from different perspectives. Although most litigation involves IP law, in particular copyright and the rights of database producers, scraping can also raise problems of data protection, unfair competition, and public or criminal law. Besides, many of such issues may fall into the gaps of the legal system. Accordingly, the paper aims to provide an overall framework for the ethical and legal issues of scraping, to take sides between ‘good’ and ‘bad’ uses of technology and, on this basis, flesh out the legal hard cases of the field.